Engineering therapeutic T cells to suppress alloimmune responses using TCRs, CARs, or BARs. Issue 6 (21st April 2018) - Sicard, Antoine; Levings, Megan K.; Scott, David W.
Abstract : Adoptive cell therapy with therapeutic T cells has become one of the most promising strategies to stimulate or suppress immune responses. Using virus‐mediated genetic manipulation, the antigen specificity of T cells can now be precisely redirected. Tailored specificity has not only overcome technical limitations and safety concerns but also considerably broadened the spectrum of therapeutic applications. Different T cell–engineering strategies have now become available to suppress alloimmune responses. We first provide an overview of the allorecognition pathways and effector mechanisms that are responsible for alloimmune injuries in the setting of vascularized organ transplantation. We then discuss the potential to use different T cell–engineering approaches to suppress alloimmune responses. Specifically, expression of allospecific T cell receptors, single‐chain chimeric antigen receptors, or antigen domains recognized by B cell receptors (B cell antibody receptors) in regulatory or cytotoxic T cells are considered. The ability of these strategies to control the direct or indirect pathways of allorecognition and the cellular or humoral alloimmune responses is discussed. An intimate understanding of the complex interplay that occurs between the engineered T cells and the alloimmune players is a necessary prerequisite for the design of safe and successful strategies for precise immunomodulation in transplantation. Abstract : This review discusses the potential use of different T cell engineering approaches to suppress alloimmune responses.